2022
DOI: 10.1039/d1tc05538k
|View full text |Cite
|
Sign up to set email alerts
|

In situ, seed-free formation of a Ruddlesden–Popper perovskite Cs2PbI2Cl2 nanowires/PbI2 heterojunction for a high-responsivity, self-powered photodetector

Abstract: As the necessary precursor of emerging lead‐halide perovskite materials, PbI2 is also promising for optoelectronic devices, such as photodetectors (PDs). Herein, the novel Ruddlesden-Popper (RP) perovskite Cs2PbI2Cl2 nanowires is grown...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…It is found that the current rapidly arrives at a relatively large value and then decreases slowly to a stable saturation value. This is a widely observed feature, and it is also observed in PbI 2 photodetectors, ,, which is usually called “transient photocurrent response” or “the initial overshoot phenomenon”. Generally, this phenomenon is attributed to charge accumulation and the continuous generation of carriers under irradiation. , When switching the light on, a large number of photogenerated electron–hole pairs quickly generate at a narrow time scale, and the current reaches up to a peak value quickly, which is higher than the stabilized current because the transient carrier time is much faster than the recombination lifetime.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…It is found that the current rapidly arrives at a relatively large value and then decreases slowly to a stable saturation value. This is a widely observed feature, and it is also observed in PbI 2 photodetectors, ,, which is usually called “transient photocurrent response” or “the initial overshoot phenomenon”. Generally, this phenomenon is attributed to charge accumulation and the continuous generation of carriers under irradiation. , When switching the light on, a large number of photogenerated electron–hole pairs quickly generate at a narrow time scale, and the current reaches up to a peak value quickly, which is higher than the stabilized current because the transient carrier time is much faster than the recombination lifetime.…”
Section: Resultsmentioning
confidence: 83%
“…From the UPS spectrum in Figure a, the cutoff energy boundary ( E cutoff ) and onset boundary ( E onset ) of the Si wafer are 16.22 and 0.13 eV, respectively. According to the equations of E v = −[21.22 – ( E cutoff – E onset )] and E F = −(| E v | – E onset ), the valence band ( E v ) and Fermi level ( E F ) are calculated to be −5.13 and −5.00 eV, respectively. , According to the band gap (E g ) value of Si (1.12 eV) reported in the literature, the conduction band (E c ) value of the Si wafer is −4.01 eV. Similarly, the band structure of PbI 2 can be deduced from the UPS spectrum, as demonstrated in our previous work, where the values of E c , E v , and E F are −3.76, −6.16, and −5.47 eV, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…The device shows an R of 0.31 A W −1 and a D * of 2.87 × 10 12 Jones under weak light (5 × 10 –5 mW cm −2 ): These values are larger than the reported micro/nanostructure PDs and are comparable to other high‐performance perovskite PDs. [ 26–29 ]…”
Section: Resultsmentioning
confidence: 99%
“…1,2 Applications of 2D Cs 2 PbI 2 Cl 2 in optoelectronic devices, such as photodetectors and LEDs, have also been explored. 8,11,13,16 According to the conclusion proposed by Giustino et al, high carrier mobilities can be anticipated for 2D Cs 2 PbI 2 Cl 2 because of the in-plane Pb−Cl framework. 17 We also confirmed this point by predicting a rather high electrondominated carrier mobility for 2D Cs 2 PbI 2 Cl 2 (as high as ∼9.39 × 10 3 cm 2 V −1 s −1 ) based on the deformation-potential theory.…”
mentioning
confidence: 94%
“…All-inorganic two-dimensional (2D) perovskites have attracted considerable interests due to their potential to exhibit superior robustness under extreme conditions compared to hybrid organic–inorganic perovskites. Additionally, inorganic 2D perovskites also exhibit promising optoelectronic properties, such as small in-plane effective carrier masses, low exciton binding energies, and high carrier mobilities due to the elimination of large organic interlayer spacers. These properties suggest their potential application in high-performance optoelectronic devices, such as spintronic devices, photodetectors, transistors, and light-emitting diodes (LEDs).…”
mentioning
confidence: 99%